The recognition of filiation relationships in the European Union: the free movement of birth certificates issued in a member state. Around the STJUE Pacharevo and the ATJUE K.S.-S.V.D. - Goñi Urriza, Natividad (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
The Order of the Court of Justice of June 24, 2022 in K.S.-S.V.D. confirms the judgement of the Pancharevo case awarded six months before and obliges Member States to recognize the parentchild relationship established between a minor and her two mothers in a Member State for the sole purpose of issuing the documents necessary for them to exercise their right to free movement and residence.
Keywords: Right to move and reside freely within the territory of the Member States; transcription of birth certificate; child rights for private and family life and to maintain on a regular basis a personal relationship and direct contact with both his or her parents